Topics in Foreign Language Teaching in Research Articles in Psycholinguistics: Reviewing the State-of-the-Art - Kapranov, Oleksandr (Verbum, 2023)
The article introduces a study whose purpose is to provide a review of research articles (RAs) in psycholinguistics which focus on foreign language teaching (FLT). To that end, the study examines a corpus of RAs in psycholinguistics that address FLT-related research topics, which are published in two international peer-reviewed journals, namely Psycholinguistics and Eastern European Journal of Psycholinguistics. The corpus was examined for the presence of research topics in FLT, as well as the RAs’ bibliometric data. The results of the corpus analysis revealed that the majority of the RAs were single-authored by female researchers, who focused on such FLT-related research topics as translation and interpreting, speaking in a foreign language (FL), and FL proficiency. It was established that the FLT-themed RAs investigated primarily English as a Foreign Language (EFL) and, less frequently, German, Chinese, Japanese, Latin, and Ukrainian. The findings are further described and discussed in the article.